Hubungan Aktivitas Fisik, Psikologis , Dan Sosial Dengan Kualitas Hidup Penderita Atrial Septal Defect Closure Usia 19 – 45 Tahun Di Yayasan Hipertensi Paru Indonesia Tahun 2023 - Rahma Dati Badillah; Eka Rokhmiati Wahyu Purnamasari; Hari Ghanesia Istiani (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
Atrial Septal Defect (ASD) is a common congenital heart defect in adults, often undetected early due to lack of symptoms. Patients with ASD who have undergone closure experience physical limitations and low physical activity, also face low psychological and social conditions. Therefore, they need social and emotional support. This study examined the relationship between physical, psychological, and social activities with quality of life in patients with ASD Closure at the Indonesian Pulmonary Hypertension Foundation. The cross-sectional research method involved 30 adults (19-45 years old). The results of the study with Spearman Rank and chi square showed a significant relationship between physical activity (p value 0,00 < 0.05), psychological aspects (p value 0,00 < 0.05), and social aspects (p value 0.00 < 0.05) with quality of life. This study is expected to provide benefits for ASD closure patients in improving their quality of life